Dynamic analysis of flashover in high voltage DC polluted insulator - Astorga, Oscar A. Maldonado [UNESP]; Filho, Jose Pissolato (Institute of Electrical and Electronics Engineers (IEEE), 1992)
The actual voltage growing in electrical power systems make the insulation studies, very important. In this, one of the principal problems is the development of discharges in surface polluted high tension insulators. Under some conditions, this discharges may increase between the high voltage and the ground causing the appearancement of flashover phenomena which can lead even to system's lost. The know]edgement of flashover dynamic behaviour, is important to develop maintenance, operation and design technics that lead to improve the performance of high voltage insulators working in polluted regions.